The Impact Of Family Functioning On The Effectiveness Of Family Based Diabetes Prevention Programs - Mohamed Elnozhe, Faten Mohamed; Abd ElHay, Amira E. M.; Mousa, Mai E.; Yousef, Abeer M.; Borham Hussein, Mohamed Rafat; Elzoghby, Hanaa Mohamed; Hamouda, Noha Mohamed Afifi; Mohamed Mazen, Mohamed; Abdelkader, Samiha M. I.; Darwesh, Alshimaa Mokhtar (International Journal of Aquatic Research and Environmental Studies, 2026)
Background : Family functioning is a family’s ability to communicate, solve problems, carry out tasks and support each other. Unhealthy family functioning may be a risk factor for obesity and non treatment of chronic diseases. Fair Haven Community Health Center, a federally qualified health center in New Haven serving a patient population with high rates of obesity and diabetes, holds screenings for prediabetes and based Diabetes Prevention Program adherence to diabetes to identify patients who are eligible to participate in the family (DPP) for prediabetic adults and the Bright Bodies (BB) program for overweight children . . Hypotheses: Unhealthy family functioning is associated with obesity and a diagnosis of prediabetes or diabetes at diabetes screenings. Unhealthy family functioning is associated with suboptimal enrollment, attendance, participation based DPP/BB program will improve family functioning Methods: . -- and weight loss in the DPP/BB program. The family We enrolled participants at diabetes screenings in an observational cohort study. To assess family functioning, we administered the General Functioning subscale GF). We measured participants’ BMI and performed metabolic testing, including 2 enrollment, participation and outcomes in the DPP/BB program 73 of the McMaster Family Assessment Device (FAD hour oral glucose tolerance testing. We followed participants for subsequent Results: We enrolled 129 participants ages 13 at diabetes screenings. Just over half of participants (53%) had unhealthy family functioning, defined as a baseline FAD-GF score > 2.0. Participants with private insurance had healthier family functioning scores than participants with Medicaid (p = 0.012). Healthy family functioning was significantly correlated with higher BMI 0.257, p = 0.009. There was no association between family functioning and a in adult participants, r (102) = .-- sample (n=14), participants with healthy family diagnosis of prediabetes or diabetes. In a small longitudinal sub functioning lost significantly less weight during the program compared to participants with unhealthy family .functioning (-0.61 + 3.83 lbs vs. -5.02 + 3.21 lbs), p = 0.042. Conclusion: Unexpectedly, healthy family functioning may be a risk factor for adult obesity in this predominantly Further research is necessary to validate our results and determine which factors related to families, food and culture might explain the link between healthy family functioning and obesity